A Study on Theoretical Framework for the Sustainable Development of Tourism Using Diamond Model - Adillón , Ramón (An Overview on Business, Management and Economics Research Vol. 3, 2023)
In order to ensure a sufficient development of the tourism activity without endangering the future of the tourism product itself, the paper introduces the diamond sustainable tourism development model. This model aims to provide objective criteria to help organizations to take the necessary decisions about controlling the number of visitors to a tourism destination or attraction. The scholarly literature on the negative effects of tourism is reviewed in this essay, along with different approaches that have been utilized to handle the problem of tourism congestion. The report also makes the case that a few important factors, such as destination carrying capacity, resident community quality of life, and visitor experience, ought to be given more explicit consideration.